2012
DOI: 10.1080/14789949.2012.704639
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a national sample of homicides committed by lone and multiple perpetrators

Abstract: Homicide committed by multiple perpetrators is an understudied area and there has been no research investigating psychiatric differences between multiple and lone perpetrators of homicide. The objective of this study was to explore the demographic, criminological and psychiatric differences of the victims and perpetrators of multiple perpetrator homicides and compare them with the victims and perpetrators of lone perpetrator homicides. A 10-year (1997-2006) consecutive national sample of homicide perpetrator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…Some of the results obtained from the pre‐incarceration analyses were consistent with findings from previous research that utilized mixed samples of juveniles and adults. Similarly to prior studies, the data indicated that group offenders were more likely to target a stranger (Clark, ; Roscoe et al, ) and perpetrate homicide during the commission of another crime (Block, ; Cheatwood & Block, ). The finding that group offenders were more likely than lone JHOs to have a prior criminal record (83% vs. 56%) supports what Clark () found in his multi‐city sample.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Some of the results obtained from the pre‐incarceration analyses were consistent with findings from previous research that utilized mixed samples of juveniles and adults. Similarly to prior studies, the data indicated that group offenders were more likely to target a stranger (Clark, ; Roscoe et al, ) and perpetrate homicide during the commission of another crime (Block, ; Cheatwood & Block, ). The finding that group offenders were more likely than lone JHOs to have a prior criminal record (83% vs. 56%) supports what Clark () found in his multi‐city sample.…”
Section: Discussionsupporting
confidence: 66%
“…Previous comparative research has found several differences between lone and group murderers with respect to demographic, homicide offense, and behavioral characteristics, using samples that contained both juvenile and adult offenders. Compared with lone murderers, group murderers tended to be younger (either juveniles or younger adults and juveniles) (Cheatwood & Block, ; Clark, ; Cornell, ; Juodis, Woodworth, Porter, & Ten‐Brinke, ; Roscoe et al, ), committed homicide in conjunction with other felonies, such as robberies (Block, ; Cheatwood & Block, ; Clark, ; Juodis et al, ), and were more likely to target strangers (Clark, ; Roscoe et al, ). Inconsistent findings emerged with respect to criminal history.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Homicide offenders tend to be also recidivist offenders, often not necessarily in terms of homicide reoffending but in terms of general delinquent recidivism (Liem, 2013). About a quarter of homicides are committed by multiple perpetrators (Roscoe et al, 2012). Both murderers and their victims amount to high costs to society: DeLisi et al (2010) reported that the average cost per murder exceeds $17.25 million; in addition, the average murderer poses costs approaching $24 million.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, juvenile offenders were more likely than adults to offend in the context of a group (or with at least one other offender) as opposed to acting alone. Furthermore, research conducted in other countries (i.e., England and Wales) also found that multi-offender homicides were more likely to be committed by younger offenders (Roscoe et al 2012).…”
Section: Discussionmentioning
confidence: 98%